2018
DOI: 10.1186/s12876-018-0811-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic value of cell-cycle-associated genes in gastric adenocarcinoma

Abstract: BackgroundGastric carcinoma is a malignant disease, and gastric adenocarcinoma (GAC) is the most common histological type. Molecular profiling of GAC has been extensively performed, but few have focused on the clinical significance of gene clusters of the cell cycle.MethodsWe investigated the genetic profile of cell-cycle-associated genes in a GAC cohort. The mRNA expression and clinical data were downloaded from TCGA, according to cBioportal. We conducted a series of analyses to detect the relationships betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Amplifications mainly targeted well-known oncogenes such as EGFR , ERBB2 , KRAS , MYC , CCNE1 , JAK2 , FGFR2 et al 12 gastric tumor tissues harbored CCNE1 amplifications (7.84%), which was the most frequent genes with SCNA in this study, and with similar frequency (10.58%) in TCGA cohort [4]. Amplification of CCNE1 is associated with poor outcome in gastric [23], breast [24], and ovarian cancer [25, 26]. ERBB2 amplification was detected in 8 gastric tumor tissues (5.23%).…”
Section: Resultsmentioning
confidence: 57%
“…Amplifications mainly targeted well-known oncogenes such as EGFR , ERBB2 , KRAS , MYC , CCNE1 , JAK2 , FGFR2 et al 12 gastric tumor tissues harbored CCNE1 amplifications (7.84%), which was the most frequent genes with SCNA in this study, and with similar frequency (10.58%) in TCGA cohort [4]. Amplification of CCNE1 is associated with poor outcome in gastric [23], breast [24], and ovarian cancer [25, 26]. ERBB2 amplification was detected in 8 gastric tumor tissues (5.23%).…”
Section: Resultsmentioning
confidence: 57%
“…Nevertheless, it has also been reported that ESPL1 plays an opposite role in gastric adenocarcinoma. Wang D. et al (2018) showed that ESPL1 levels were lower in gastric adenocarcinoma tissue in comparison with that of adjacent non-cancer tissue and was associated with longer overall survival and a low tumor stage suggesting the dual role of this gene in cancer. ESPL1 expression was found to be increased in our study, however, the clinical significance and functional mechanism of ESPL1 in EC remains to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has also been reported that ESPL1 plays an opposite role in gastric adenocarcinoma. ESPL1 expression was negatively correlated with gastric adenocarcinoma pathologic stage progression, and the high expression of ESPL1 was signi cantly correlated with favorable outcomes [35]. Further work is required to resolve the con icting roles of ESPL1 in cancer and determine its functions in cancers including the ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%